PREDIKTOR KEBERHASILAN STUDI PADA MAHASISWA DI FAKULTAS PSIKOLOGI UIN SUNAN GUNUNG DJATI BANDUNG - Fenti Hikmawati; Nani Nuranisah Djamal; Agus Abdul Rahman; Elisa Kurniadewi (Psympathic : Jurnal Ilmiah Psikologi, 2010)
This study will specifically investigate the personal factors of students, whether they are biographic, or suspected psychological effect on the success of studies in the faculty of Psychology. Demographic factors such as intelligence level factors, whether the school background of high school, vocational school, or MA, and majors of time in SMU / SMK / MA. These factors are investigated for allegedly influence the success of the study. If proven, empirically, the results of this study expected to be a consideration in the selection of new students of psychology faculty UIN Sunan Gunung Djati Bandung. During this selection system seems not yet to consider these factors. In fact, psychological test results of students' 2007-2008 force distribution of the IQ level of students was very varied between 78 to 115 points. Not much different school backgrounds and majors. The design of this study applying correlational design, multiple regression. With multiple regression, it is possible to forecast a variable based on the values of some predictors. The assumption by using several predictors will make more accurate predictions. In addition, with multiple regression is statistically possible to measure the influence of several predictor variables to control the other predictor variables (Blaikie, 2003). Research data, including: (1) The primary data is data related to emotional intelligence and social support, and (2) secondary data id data relating to the level of intelligence. Secondary data were obtained from laboratory psycho-tests held by the faculty of Psychology UIN SGD Bandung and the data contained in the faculty of Psychology UIN SGD Bandung. Results of data analysis shows that the correlation coefficient of the three independent variables with dependent variables for 0409 with a value of R2 of 0167. It shows that 16.7 percent of the variation of study success is determined by emotional intelligence, social support, and level of intelligence. Level intelligence backgrounds of students majoring in natural science majors were higher than social science or language. Meanwhile, 83.3 percent more determined by other variables.